COMPARISON OF TOTAL ANTIOXIDANT CAPACITY (TAC)’S PATIENTS OF CHRONIC KIDNEY DISEASE UNDERGOING HEMODIALYSIS AND NON-HEMODIALYSIS - Zaky Firmawan El-Hakim; Mochammad Thaha; Yetti Hernaningsih (Majalah Biomorfologi, 2020)
Background: Total antioxidant capacity (TAC) is one of the biomarkers to determine a person's health condition through antioxidant and oxidant activity or oxidative stress so that it can help in determining the therapy needed. However, currently, TAC levels in patients with chronic kidney disease (CKD) undergoing hemodialysis (HD) and non-hemodialysis (non-HD) are still controversial, so further research is needed. Objective: To analyze the comparison of TAC in HD and non-HD CKD patient. Materials and Methods: This was an analytical cross-sectional study with clinical observation in CKD patient. A total of 71 CKD patients consisting of 28 CKD HD patients and 43 non-HD CKD patients were enrolled in this study. Data about the characteristics of the subjects were taken using the anamnesis method, while data about TAC were taken using the colorimetric method with COBAS C-501 0837-19 series and 0835-13 series to measure TAC levels in the serum of CKD patients. The data that has been obtained were analyzed using independent sample t-tests. Results: TAC levels were significantly higher in CKD patients undergoing HD compared to non-HD CKD patients (p <0.05). There are data on albumin as an antioxidant and MDA as an oxidative stress biomarker that affects TAC levels. Conclusion: TAC levels found to be higher in hemodialysis CKD patient compared to non-hemodialysis CKD patient.